THE ROLE OF POLITICAL PARTIES AS UPHOLDERS OF DEMOCRACY IN INDONESIA - Zainul Djumadin (Sean Institute, 2023)
Democracy as a form of government that involves active community participation requires a strong role for political parties as mediators between community interests and the decision-making process. Political parties in Indonesia contribute to maintaining democratic values and maintaining the balance of power between the executive, legislative and judiciary. This research aims to analyze the main role of political parties in strengthening and maintaining the health of democracy in Indonesia. This research method uses a qualitative approach with descriptive methods. The results of this research reveal that the role of political parties as enforcers of democracy in Indonesia is very significant in various aspects. Political parties act as representatives of society, forming and maintaining a democratic system through participation in general elections, and being actively involved in policy making. However, the findings also highlight challenges, such as the risk of elitism and abuse of power, that need to be addressed so that the role of political parties can be more effective in realizing inclusive and sustainable democracy in Indonesia.